Isomorphism In Context: The Power And Prescription Of Institutional Norms - Dacin, M. Tina (Academy of Management Journal, 1997)
To what extent do broadly based sociocultural norms affect the distribution of organizational characteristics within a population over time' Under what circumstances are institutional norms more important than alternative processes, such as market forces, in shaping this distribution' This sociohistorical analysis of the impact of nationalism on the language of publication of Finnish newspapers in the 19th century examines the interplay of institutional, ecological, and economic forces. The findings confirm that the power with which institutional norms influence organizations can vary over time, across levels of analysis, and as a function of ecological and economic forces and other, more proximal, sources of institutional expectations.